Mapping China's ESG Disclosure Research Evolution: A CiteSpace-Based Knowledge Visualization Analysis (2004-2024) - FeiFei, Fan; Asri, Marsidi (Global Academy of Training & Research (GATR) Enterprise, 2025)
Objective — This study aims to systematically investigate the evolutionary trajectory of Environmental, Social, and Governance (ESG) information disclosure research in China from 2004 to 2024, mapping the intellectual structures, collaboration networks, and research dynamics to identify developmental patterns and research gaps in this rapidly evolving domain. Methodology – A comprehensive bibliometric analysis was conducted using CiteSpace visualization software to analyze 1,039 academic publications sourced from the Web of Science database. The methodology employed temporal distribution analysis, author and institutional collaboration network visualization, keyword co-occurrence analysis, and burst detection to map knowledge structures and research trends. Findings – The analysis revealed three distinct developmental phases in China's ESG disclosure research: an emergence phase (2004-2014), a steady growth phase (2015-2019), and an acceleration phase (2020-2024) following China's "dual carbon" goals announcement. Critical gaps were identified in interdisciplinary collaboration and industry-academia partnerships. Research focus has shifted from conceptual frameworks toward technology-enhanced disclosure mechanisms, with emerging clusters on digital transformation, climate risk disclosures, and greenwashing detection. Novelty – This research produces the first comprehensive knowledge map of China's ESG disclosure research ecosystem using visualization techniques, providing quantitative evidence of the policy-driven nature of sustainability reporting development in emerging economies. The work uniquely bridges international ESG disclosure theories with China's distinctive institutional context while offering a methodological innovation that demonstrates how visualization techniques overcome traditional literature review limitations in complex research domains.